Comments on “Post severe COVID-19 infection lung damages study. The experience of early three months multidisciplinary follow-up” by De Michele et al. - Ruggeri, Paolo; Nair, Abhijit S.; Esquinas, Antonio (Monaldi Archives for Chest Disease, 2022)
Dear Editor, We read the original study by De Michele et al. titled “Post severe COVID-19 infection lung damages study. The experience of early three months multidisciplinary follow-up” with great interest...